Lesion Sterilization Tissue Repair and Recent Advances: A Review (Academia Journal of Medicine, 2023)
Lesion sterilization tissue repair (LSTR) is an emerging  approach in dentistry, aimed at eliminating infectious  microorganisms from the root canals and promoting  tissue repair. This review provides a comprehensive  overview of the principles, techniques, and recent  advances in LSTR. The traditional root canal treatment  focuses on complete debridement and disinfection of  the root canal system. However, LSTR offers an  alternative approach by employing a triple antibiotic  paste (TAP) consisting of metronidazole, ciprofloxacin,  and minocycline. This antibiotic combination has  shown promising results in eliminating the root canal  microbiota, particularly in cases of immature teeth  with open apices and necrotic pulps.
Keywords: Lesion sterilization tissue repair; LSTR; TAP